Efek Konflik Israel-Hamas di Indonesia: Opini Publik dan Upaya Diplomatik - Rahmawan, Rojanafira Hasna; Priyanto, Priyanto; Midhio, I Wayan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This paper explores the impact of the Israel-Hamas conflict on Indonesia by analyzing the dynamics of public opinion and diplomacy efforts. By focusing on data collected from social media and news coverage, this article dives into how social media and news coverage can shape public opinion that can lead to trends and sentiments by emphasizing their influence on discourse and perception. In addition, the article analyzes Indonesia's diplomatic initiatives in response to the Israel-Hamas conflict. The findings contribute to a different understanding of Indonesia's position in the global perspective amid the Israel-Hamas conflict.